Ultrasound-stimulated drug release from polymer micro and nanoparticles. Issue 1 (1st March 2013) - Enayati, Marjan; Mohazey, Dana al; Edirisinghe, Mohan; Stride, Eleanor
Abstract : Ultrasound-responsive drug delivery systems have great potential for applications requiring stimulated release in vivo with a high degree of control over spatial and temporal location. In this study, systematic investigations were carried out to determine the effect of various ultrasound exposure parameters, in particular, output power, duty cycle and exposure time, on the release rate of a model drug (estradiol), encapsulated in poly DL-lactide-co-glycolide particles of different sizes prepared using electrohydrodynamic processing. The effect of ultrasound exposure on the degradation and surface morphology of the particles was also studied through optical and electron microscopy. There was found to be a positive correlation between drug release and each of the ultrasound parameters investigated, with output power having the most significant effect on both release rate and the morphology of the particles. The increase in surface porosity observed indicates that degradation may be attributed to cavitation phenomena. Ultrasound responsive drug delivery systems have great potential for applications requiring stimulated release in vivo with a high degree of control over spatial and temporal location. In this study, systematic investigations were carried out to determine the effect of various ultrasound exposure parameters, in particular, output power, duty cycle and exposure time, on the release rate of a model drug (Estradiol), encapsulated in Poly DL‐lactide‐co‐glycolide (PLGA) particles of different sizes prepared using electrohydrodynamic processing. The effect of ultrasound exposure on the degradation and surface morphology of the particles was also studied through optical and electron microscopy. There was found to be a positive correlation between drug release and each of the ultrasound parameters investigated, with output power having the most significant effect upon both release rate and the morphology of the particles. The increase in surface porosity observed indicates that degradation may be attributed to cavitation phenomena